Understanding liberal democracy essays in political philosophy - Wolterstorff, Nicholas; Cuneo, Terence, 1969- (Oxford : Oxford University Press, 2012)
This volume presents influential work by Nicholas Wolterstorff at the intersection between political philosophy and religion alongside nine new essays on the nature of liberal democracy human rights, and political authority. These essays offer an alternative to the public reason liberalism defended by thinkers such as John Rawls.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Democracy; Liberalism; Political science -- Philosophy